In vitro lipoxygenase and hemolysis inhibition by polyphenolic antioxidants from tropical green leafy vegetables - Bhatt S, Kavya; Nanjarajurs M, Shashirekha; M. Eligar, Sachin (Emirates Journal of Food and Agriculture, 2022)
Consumption of green leafy vegetables, a nutrient-dense food, is associated with protective roles in human health and a reduction in risk of cancer, cardiovascular, and other inflammatory diseases. Phytochemical components such as phenolics and flavonoids are said to contribute to these benefits. Data on the anti-inflammatory potential and phenolic content of many Indian green leafy vegetables is still scanty. We investigated eleven tropical green leafy vegetables for their phenolic and flavonoid content along with anti-inflammatory and free radical scavenging properties. Black nightshade had the lowest phenolic and flavonoid content (2.36 mg Gallic Acid Equivalents/g DW and 1.66 mg Rutin Equivalents/g DW), whereas desert horsepurslane (41.73 mg GAE/g DW) and red amaranth (27.18 mg RE/g DW) had the highest phenolic and flavonoid content, respectively. Similarly, the free radical scavenging activity for 2, 2-diphenyl-1-picrylhydrazyl (DPPH) ranged from 10.57 – 84.97 % inhibition and 50.73 – 266.48 µg Trolox Equivalents/g DW for 2, 2-azinobis-(3-ethylbenzothiazoline6-sulphonate (ABTS) decolorization assay. The phenolic and flavonoid content correlated significantly with the radical scavenging activity. The hemolysis and lipoxygenase inhibition was observed to be lowest in Amaranthus sp. and desert horsepurslane (6.08% and 53.75 %) and highest in dill and fenugreek (69.94% and 78.55 %), respectively. Overall, our study adds to the polyphenolic and antioxidant data available on green leafy vegetables, in addition to highlighting their anti-inflammatory potential